SAFE MED Quality Improvement Project: Supporting Availability and Functionality of Essential Monitoring Equipment for Drug Use in CAMHS (Child and Adolescent Mental Health Services) Outpatient Services in Oxfordshire - Sureyya Melike Toparlak; Andreea Dumitrascu; Emma Fergusson; Marta Costa; Robert Chapman (BJPsych Open)
Aims: Main aim of this quality improvement project was to ensure that each outpatient CAMHS clinic room is equipped with the necessary, functional equipment for safe and comprehensive baseline and ongoing monitoring of patients prescribed antidepressant, antipsychotic, and ADHD medications, in line with NICE guidelines, the Maudsley Prescribing Guidelines and hospital guidelines.